Pollen-based quantitative reconstructions of Holocene regional vegetation cover (plant-functional types and land-cover types) in Europe suitable for climate modelling - Trondman, A-K (Global change biology, 2015)
© 2014 The Authors Global Change Biology Published by John Wiley & Sons Ltd.